Do police–mental health co-responder programmes reduce emergency department presentations or simply delay the inevitable?. (February 2019) - Meehan, Tom; Brack, Janet; Mansfield, Yolanda; Stedman, Terry
Objective: The aim of this study was to assess the outcomes for people following intervention by a police–mental health co-responder team. Method: Individuals seen by the co-responder team were followed for 2 weeks to monitor subsequent emergency department presentations and inpatient admissions. Results: Of the 122 people who had direct contact with the co-responder team, 82 (67.2%) remained at their residence, 35 (28.7%) were transported to the emergency department (ED) and 5 (4.1%) were taken into custody by police. The 82 people who remained at home following initial assessment were followed-up for 2 weeks. During this time 10 (12.2%) presented to ED and 3 of these (3.7%) were subsequently admitted to hospital. Conclusions: Interventions provided through the co-responder team were capable not only of resolving the immediate crisis for the majority of people, but were also likely to divert people away from ED and inpatient treatment in the immediate term.